Pengembangan Keterampilan Berbahasa Inggris Siswa Melalui Kegiatan English Club di UPTD SMP Negeri 7 Kupang - Yohana Logha; Maria Astriana Kolo; Novita Ina Uba; Elvis Albertus Bin Toni (PELITA NUSA TENGGARA, 2026)
The development of students’ English speaking skills has become an essential need in the context of 21st-century education; however, not all schools have structured supporting programs. UPTD SMP Negeri 7 Kupang previously did not have an English Club extracurricular activity due to limited mentoring personnel, despite students’ high interest in learning English. This community service program aimed to initiate and assist the establishment of an English Club as a platform for developing students’ speaking skills. The English Club activities included conversation, storytelling, and speech, with a primary focus on speaking proficiency. The aspects developed encompassed fluency, pronunciation, vocabulary enrichment, and students’ confidence in speaking English. The implementation methods involved role play, pair work, games such as charades and dialogue swaps, as well as mini projects that encouraged active student participation. The stages of the program consisted of a preliminary study, program implementation, and evaluation. The results indicated the successful establishment of an English Club extracurricular program at SMP Negeri 7 Kupang, along with increased student participation and confidence in communicating in English. This activity highlights the importance of English Clubs as an effective medium for enhancing students’ speaking skills in schools.